Hubungan Pendapatan Keluarga dengan Status Gizi Balita di Desa Bojong Kecamatan Pameungpeuk Kabupaten Garut - Gantini, Tuti; Hendrawan, Hendrawan; Barkah, M. Riana (Ma'soem University, 2024)
Family income could indicate the ability of family in fulfilling food necessity. Family with higher income could get sufficient food intake for the whole family members, especially toddler, so good nutritional status would be reached. Research had been conducted in Bojong Village Subdistrict of Pameungpeuk Garut Regency to find out the relationship between family income and nutritional status of toddler. Survey method was applied in this research with samples of 30 families who still have toddlers. The relationship between nutritional status of toddler and family income was tested by the Rank Spearman. Result of the research showed that there was a strong relationship between nutritional status of toddler and family income (r 3,06 much bigger than r - table 1,70. Determination Coefficient was 85.94 meant family income gave contribution 85.94% to nutritional status of toddler.